Komunikasi Interpersonal PT. Grab dalam Peralihan Kendaraan Konvensional ke Kendaraan Listrik - Alisabana, Fernando; Sukanda, Ukon Furkon; Khairani, Aulian (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Transportation services have a very important role in human life, where transportation services are used to facilitate their daily activities. With the presence of the latest innovations in the field of transportation, one example of the latest advances in the transportation industry is the presence of a company that provides application-based online transportation services, namely Grab. Now Grab is formalizing the new look of its electric vehicle called Grab Electric. The transition of conventional vehicles to electric vehicles carried out by Grab can have a positive impact on the use of electric vehicles, namely helping to reduce carbon gas emissions. So in this case the author wants to know the interpersonal communication process at Grab to its partners. This research uses descriptive qualitative research methods based on case studies at PT Grab with data collection techniques of observation, interviews, and documentation. The theory used by researchers is the theory of Social Exchange or social exchange developed by Thibaut and Kelly. The results of this study indicate that the use of electric vehicles by driver partners has a positive impact due to lower operating costs.